Who is an employee? - Senčur Peček , Darja (Anali PAZU, 2022)
The article discusses the definiton of the employment relationship and of employee, indicators of the existence of an employment relationship, the »principle of primacy of fact« and certain categories of persons legally deemed to be either employees or self-employed. The author also deals with the question whether labour-law protection should be given only to employees or (to the certain extent) also to the third category of persons (economically dependent) or even to all persons who work for another person.
Keywords: employment relationship; employee; contract of employment; quasi employee (economically dependent)